Glucose turnover in severe falciparum malaria. - Davis, T; Looareesuwan, S; Pukrittayakamee, S; Levy, J; Nagachinta, B; White, N (1993)
To investigate glucose metabolism in acute falciparum malaria, [3-3H]glucose turnover was measured in 18 normoglycemic adult Thais (eight males, 10 females; median age, 28 years) with severe infections. Eleven patients were studied before quinine treatment, 15 while receiving quinine, and 10 during convalescence. In paired studies conducted before and after initial intravenous quinine, plasma glucose level decreased from a median (95% confidence limits) of 5.5 (3.0 to 6.6) to 4.6 (2.5 to 6.1) mmol/L (P < or = .027, n = 8), and plasma insulin level increased 9.3 (-3.2 to 30.0) mU/L (P = .02). Glucose turnover decreased during the 4-hour quinine infusion from 3.04 (2.12 to 4.23) to 1.89 (1.20 to 2.54) mg/kg.min-1 (P < .004), as did the metabolic clearance rate for glucose (2.87 [1.88 to 7.83] to 2.50 [1.43 to 4.55) mL/kg.min-1; P = .008). Glucose turnover and clearance measured both after initial quinine treatment and in convalescence were similar (P = .234 and .344, respectively; n = 7). In the series as a whole, there was an inverse association between pretreatment turnover and the simultaneous plasma glucose level (rs = -.76, P < .01; n = 11), a stronger inverse relationship between glucose clearance and plasma glucose level (rs = -.88, P < .001), and a positive association between pretreatment turnover and oral temperature (rs = .65, P < .025; n = 10). These data suggest that, as in other severe illnesses, glucose turnover is high in untreated patients, but that glycolysis by mature parasite forms may accelerate glucose disposal.(ABSTRACT TRUNCATED AT 250 WORDS)